ASSESSMENT OF MICRO-NUTRIENT POTENTIALITY AND IDENTIFICATION OF BIO ACTIVE COMPONENTS OF THE AVICENNEAALBA FRUIT (MANGROVE) IN SUNDERBAN, INDIA - RIA HALDER,; PRANABES SANYAL,; SUNITI GHOSH CHATTERJI, (International Journal of Pharma and Bio Sciences, 2016)
The Sundarban is a natural region in the Bengal region comprising Eastern India and Bangladesh. It is the largest single block of tidal halophytic mangrove forest in the world. Only a limited number of plant sp. thrive in mangrove eco-system. In Indian Sundarban the mangal vegetation comprises of 94 intertidal sp. but less than 10 sp. are utilized by the locals as food & fodder materials. Avicenna alba, is one of them .Local people of Sundarban use this fruit as vegetable. The present study was aimed to identify the various micro-nutrients and phytochemical constituents by ICP-OES analysis and GC-MS analysis. The results for the first time revealed the presence of several bioactive components in the fruit of Avicenna alba.